The 2013 Balochistan earthquake: An extraordinary or completely ordinary event?. Issue 15 (4th August 2015) - Zhou, Yu; Elliott, John R.; Parsons, Barry; Walker, Richard T.
Abstract The 2013 Balochistan earthquake, a predominantly strike‐slip event, occurred on the arcuate Hoshab fault in the eastern Makran linking an area of mainly left‐lateral shear in the east to one of shortening in the west. The difficulty of reconciling predominantly strike‐slip motion with this shortening has led to a wide range of unconventional kinematic and dynamic models. Here we determine the vertical component of motion on the fault using a 1 m resolution elevation model derived from postearthquake Pleiades satellite imagery. We find a constant local ratio of vertical to horizontal slip through multiple past earthquakes, suggesting the kinematic style of the Hoshab fault has remained constant throughout the late Quaternary. We also find evidence for active faulting on a series of nearby, subparallel faults, showing that failure in large, distributed and rare earthquakes is the likely method of faulting across the eastern Makran, reconciling geodetic and long‐term records of strain accumulation.